1876 Ala. Code 882 - (:unkn) unknown (My University, 1877)
§ 4109: Prohibited the concealed carrying of any Bowie knife, or any other knife of like kind or description, pistol, air gun, slungshot, brass knuckles, or other deadly or dangerous weapon, unless the person was threatened with, or had good reason to apprehend, an attack, or " while traveling, or setting out on a journey." Punishable by fine of $50-300 and imprisonment of not more than 6 months.
Keywords: CARRY - CONCEALED